Strategic planning, financial system management, and performance in higher education institutions - Garad, Askar; Yaya, Rizal; Pratolo, Suryo; Rahmawati, Alni; Ateeq, Ali; Al-Absy, Mujeeb Saif Mohsen; Almuraqab, Nasser A. Saif; Danish, Fajer (Frontiers in Education, 2025)
PurposeThis study aims to experimentally evaluate the effects of strategic planning and financial system management on the performance of higher education institutions. Additionally, it examines how financial system management mediates the relationship between strategic planning and organizational performance in higher education (HE).Design/methodology/approachThis study adopts a quantitative approach. Offline and online questionnaires were distributed to academic staff at private universities in Indonesia to gather data for hypothesis testing. The SPSS macro was used to analyze responses from 249 participants and assess the proposed associations.FindingsThe findings indicate that strategic planning and financial system management have a direct impact on institutional performance. Strategic planning exerts a significant and positive influence on financial system management. Furthermore, financial system management serves as a significant mediating variable in the relationship between strategic planning and organizational performance.Practical implicationsTo effectively implement quality management in higher education, administrators must recognize the distinct roles of strategic planning and financial system management in improving organizational performance. To achieve optimal performance, higher education institutions must allocate resources to establish robust strategic planning and financial management practices.Originality/valueAlthough numerous studies have explored the relationship between strategic planning and organizational performance in higher education, research on financial system management in this context remains limited. This study is among the first to adopt a multidimensional approach to both strategic planning and financial system management in higher education, providing insights into their interdependence and practical significance for institutional leaders.